2021
DOI: 10.3390/su13031389
|View full text |Cite
|
Sign up to set email alerts
|

Can Existing Theories Explain China’s Outward Foreign Direct Investment in Belt and Road Countries

Abstract: This study examines the extent to which existing foreign direct investment (FDI) theories apply to Chinese investment in the Belt and Road Initiative (BRI) countries. This is important because existing explanations of Chinese outward FDI (OFDI) generally make scant reference to these theories. By using OFDI data for BRI countries between 2003 and 2017, we tested hypothesizes applicable to existing theories by using both pooled ordinary least squares (PLOS) and stochastic frontier analysis (SFA) methods. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Since the entry into the WTO, China has established cooperation and trade relations with more and more countries in the world, and the export-oriented economy continues to develop. Foreign direct investment plays an important role in international economic and trade cooperation [1]. Over the past decade, China's foreign direct investment has developed rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Since the entry into the WTO, China has established cooperation and trade relations with more and more countries in the world, and the export-oriented economy continues to develop. Foreign direct investment plays an important role in international economic and trade cooperation [1]. Over the past decade, China's foreign direct investment has developed rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Gautam et al [13] found no causal linkage between exchange rate and FDI inflow in China. For the fourth type of conclusion, scholars hold that the estimated influence of exchange rate on FDI inflow depends on the exchange rate system, economic structure, estimation characteristics, and the modelling approach [14,15]. To a certain extent, the fourth type of analysis can explain the inconsistency of empirical research conclusions based on the data from different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the ownership advantage of eclectic does not provide a vivid explanation for such investments in emerging economies. Furthermore, due to high labor costs, manufacturing costs, and high transaction costs in developed economies compared to southern economies, location and internalization advantages also do not fully explain OFDI in emerging economies (Chang et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic factors such as labor, capital mobility, and human capital have significant positive implications for OFDI, both in developed and southern countries (Freckleton et al, 2012 ). Although the existing OFDI theories are derived from northern countries, Chang et al ( 2021 ) tested existing theories by using stochastic frontier analysis (SFA) methods and Pooled ordinary least squares (PLOS). The results show that most existing theories apply to China’s OFDI.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation